2017
DOI: 10.1038/oncsis.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

miR-200b inhibits proliferation and metastasis of breast cancer by targeting fucosyltransferase IV and α1,3-fucosylated glycans

Abstract: Aberrant protein fucosylation is associated with cancer malignancy. Fucosyltransferase IV (FUT4) is the key enzyme catalyzing the biosynthesis of α1,3-linkage fucosylated glycans carried by glycoproteins on the cell surface, such as the tumor-associated sugar antigen Lewis Y (LeY). An abnormal increase in the levels of FUT4 and LeY is observed in many cancers and correlated with cell proliferation and metastasis. Some microRNAs (miRNAs) are known to negatively regulate gene expression. FUT4 is an oncogenic gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 55 publications
4
35
1
Order By: Relevance
“…Numerous studies have revealed that an miRNA subset is aberrantly expressed in nearly all human cancer types, including breast cancer (32)(33)(34). The dysregulation of miRNAs is involved in the tumorigenesis and progression of breast cancer due to their negative regulation of downstream target genes (35)(36)(37). It is generally accepted that miRNAs may have tumor-suppressive or oncogenic roles in breast cancer and participate in the regulation of numerous cellular biological processes (16,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that an miRNA subset is aberrantly expressed in nearly all human cancer types, including breast cancer (32)(33)(34). The dysregulation of miRNAs is involved in the tumorigenesis and progression of breast cancer due to their negative regulation of downstream target genes (35)(36)(37). It is generally accepted that miRNAs may have tumor-suppressive or oncogenic roles in breast cancer and participate in the regulation of numerous cellular biological processes (16,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant fucosylation and dysregulation of FUTs have been frequently found in human cancer [29,30]. FUT4 could catalyze α1, 3-fucosylation that is particularly involved in a variety of pathological processes and in cancer biology [31]. Importantly, cancer-related CD15/ FUT4 is overexpressed in most of metastatic colorectal cancer (mCRC) patients and participates in cetuximab or bevacizumab mechanisms of resistance in mCRC patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our lab was found a critical role of mir200b in the inhibition of breast cancer proliferation and metastasis by targeting fucosyltransferase IV and α 1,3-fucosylated glycans [37]. Previously, we reported that Rg3 drug stimulated gastric cancer cell apoptosis through FUT4 fucosylation by regulating SP1 and HSF1 expressions, which suggested oncogenic role of CagA in development of H. pylori associated gastric cancer [34], [35].…”
Section: Discussionmentioning
confidence: 92%